Management of the Amniotic Band Syndrome with Cleft Palate: Literature Review and Report of a Case - Carolina Cortez-Ortega; José Arturo Garrocho-Rangel; Joselín Flores-Velázquez; Socorro Ruiz-Rodríguez; Miguel Ángel Noyola-Frías; Miguel Ángel Santos-Díaz; Amaury Pozos-Guillén (Case Reports in Dentistry)
Amniotic Band Syndrome (ABS) is a group of congenital malformations that includes the majority of typical constriction rings and limb and digital amputations, together with major craniofacial, thoracic, and abdominal malformations. The syndrome is caused by early rupture of the amniotic sac. Some of the main oral manifestations include micrognathia, hyperdontia, and cleft lip with or without cleft palate, which is present in 14.6% of patients with this syndrome. The purpose of this report was to describe the clinical characteristics and the oral treatment provided to a 6-month-old male patient affected with ABS with cleft lip and palate.